ANALISIS KONFLIK TENURIAL TAMAN WISATA ALAM BUKIT KABA KABUPATEN KEPAHIANG - Ayu Wijayanti; Reinaldi Reinaldi; Jamaludin Winarhadi Kusumo (Jurnal Analisa Sosiologi, 2024)
This research was conducted to find out about land conflicts that had occurred for a long time and disturbed the people around the Bukit Kaba Nature Park area, Kepahiang Regency, which resulted in the arrest of several residents around the area. This study uses a descriptive qualitative method with data collection techniques in the form of interviews, FGDs and observations, which are then analyzed using a rapid land tenure assessment and conflict theory by Ralf Dahrendorf to identify the parties involved, the power of attorney, governance, and licensing arrangements in the area. The results determined that the parties involved were transmigrant communities, ministries in charge of forestry, Bengkulu provincial government, the Bengkulu BKSDA, the Bengkulu Provincial Ombudsman, the District Head, forest rangers, Sub-District Head, Kepahiang Police Chief, Village government, private parties, and Akar Foundation. The involvement of several of these parties has an impact on power, governance and licensing arrangements, where researchers found that there was conflict between the government and the transmigrant community in the distribution of managed land as a result of changes in territorial status and changes in the types of plants allowed to be planted, resulting in restrictions on the community's economic activities. According to the regulations in effect at the time.